2022
DOI: 10.3390/nu14040840
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Beverage Intake in Low-Income, Overweight, or Obese Pregnant Women

Abstract: This study examined consumption proportions and factors associated with sugar-sweetened beverages (SSBs), artificially sweetened beverages (ASBs), and 100% fruit juice (FJ) consumption. We recruited Non-Hispanic Black (n = 136) and White (n = 192) low-income overweight or obese pregnant women aged 18 to 46 years (mean = 25.7 years) from the Special Supplemental Nutrition Program for Women, Infants, and Children clinics in Michigan, USA. Independent variables included weight status, trimester, smoking, stress, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
1
4
1
Order By: Relevance
“…This agreed with a study that found an increased trend of high levels of SSBs consumption in low and middle income countries (3).The magnitude of SSBs consumption in this study is also consistent with a study in Australia that shows that the past week prevalence of pre-packaged drinks containing free sugar among adult population aged 18 + was 47.3% (24). This is also consistence with a study conducted among lowincome, overweight or obese pregnant women in western and southern Michigan, which revealed 48.2% consumption of SSBs (32).However the nding of the present study is lower than a study conducted among adult population in India that revealed 96.3% prevalence of SSBs. This discrepancy might be because of the difference in the study population i.e.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This agreed with a study that found an increased trend of high levels of SSBs consumption in low and middle income countries (3).The magnitude of SSBs consumption in this study is also consistent with a study in Australia that shows that the past week prevalence of pre-packaged drinks containing free sugar among adult population aged 18 + was 47.3% (24). This is also consistence with a study conducted among lowincome, overweight or obese pregnant women in western and southern Michigan, which revealed 48.2% consumption of SSBs (32).However the nding of the present study is lower than a study conducted among adult population in India that revealed 96.3% prevalence of SSBs. This discrepancy might be because of the difference in the study population i.e.…”
Section: Discussionsupporting
confidence: 91%
“…Women with primary and secondary education were more likely to consume SSBs compared with women with no education. In contrast to the nding of this study, a study conducted among low-income, overweight or obese pregnant women in western and southern Michigan, and among adults aged 18-30 years in Australia highlighted that individual with low educational status were more likely to consume SSBs (32,38).This discrepancy might be explained by the difference in awareness of healthy food choice between women from high income (Michigan, Australia) and low income (Africa) countries.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Some contributing factors to the change include altered olfaction and tastes, hormone fluctuations, personality traits, cultural beliefs, but mostly maternal fetal health concerns 37 39 . Others found correlations with socioeconomic status, race, stress, body mass index and education levels, although results were inconsistent 6 , 15 , 33 , 36 , 40 42 . Whether or not the attitude for SSB also plays a role in pregnant women’s beverage selection process is a topic of interest (Fig.…”
Section: Introductionmentioning
confidence: 98%
“…Studies have reported the factors associated with maternal SSB consumption, including pre-gravid tobacco use, being unmarried, low income, maternal age, parity, and socioeconomic status [ 10 , 37 ]. Other risk factors for SSB consumption during pregnancy include younger maternal age, lower education, household income, parity, socioeconomic status, country of birth and prolonged television viewing [ 30 , 39 , 44 ]. However, this evidence emanated from developed countries, mainly North America and Europe.…”
Section: Introductionmentioning
confidence: 99%